Relationship Between Clarke’s Angle and Radiological Severity of Knee Osteoarthritis: A Cross-Sectional Study - Siahaan, Henoch Gugun Parulian; Siahaan, Yusak Mangara Tua; Pradhana, Tasya Meidy (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Knee osteoarthritis (OA) is a degenerative joint disease causing disability, especially in older adults. Flatfoot, marked by reduced medial arch height, alters lower limb biomechanics and may influence knee OA severity. Objective: To evaluate the association between foot arch, measured by Clarke’s angle, and knee OA severity based on the Kellgren-Lawrence (K-L) grading to provide clinical insight for guiding management decisions. Methods: A cross-sectional study of 57 knee OA patients at Siloam Karawaci Hospital was conducted. Clarke’s angle was measured using ink footprints, and K-L grading assessed radiological severity. Statistical tests included Kolmogorov-Smirnov, one-way ANOVA, and Kruskal-Wallis, with p < 0.05 considered significant. Results: Most participants were female (77.2%) with a mean age of 65.85 ± 9.69 years. OA severity was mostly mild to moderate (K-L 2 and 3). Flatfoot prevalence was 47.4%, and lower Clarke’s angles were significantly associated with higher K-L grades (p = 0.029). No significant differences in age or BMI were found across severity groups, though BMI trended higher with severity. Conclusion: Lower Clarke’s angle correlates with increased knee OA severity. Flatfoot may contribute to or result from OA progression. Further research is needed to clarify causation and inform management strategies.